Features Of Machining Machine Parts On Cnc Machines Productivity And Accuracy - Rubidinov Shoxrux G'ayratjon o'g'li (Genius Publishing Group, 2022)
This article investigates a way to reduce the impact of working time on the processing of operator housing parts while increasing the productivity of software-controlled digital machines in the process of machine learning. Effective methods have been developed to improve the accuracy of processing by introducing additional codes into the control software
Keywords: Machine tools; numerical; increased; productivity